2022
DOI: 10.3126/njhs.v2i1.47157
|View full text |Cite
|
Sign up to set email alerts
|

Study of Glycated Haemoglobin and Lipid Profile in Type-2 Diabetes Mellitus

Abstract: Introduction: Diabetes Mellitus is characterized by chronic hyperglycemia with disturbances of carbohydrate, fat, and protein metabolism resulting from defects in insulin secretion, insulin action, or both. Objective: To compare the biochemical parameters which included glycated hemoglobin, serum total cholesterol, triglyceride, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol of people with diabetes mellitus and matched nondiabetic controls. Methods: The cross-sectional hospital-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In agreement with the study by Young KA et al who have shown the association of TG/ HDL ratio withβ cell functionand insulin sensitivity. 16 The current study revealed the increment of TG, TC, LDL, and decrement of serum HDL when compared with the healthy subjects, these findings are consistent with a study conducted at Khammam, Andra Pradesh, India by Yadav T et al 17 However, they didn't report the correlation of the TG/HDL ratio with glycated hemoglobin in their study population.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with the study by Young KA et al who have shown the association of TG/ HDL ratio withβ cell functionand insulin sensitivity. 16 The current study revealed the increment of TG, TC, LDL, and decrement of serum HDL when compared with the healthy subjects, these findings are consistent with a study conducted at Khammam, Andra Pradesh, India by Yadav T et al 17 However, they didn't report the correlation of the TG/HDL ratio with glycated hemoglobin in their study population.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in accordance with a study which also revealed reduced ABCA1 expression in type 2 diabetic study participants 22 . HbA1c has been found to be a good diagnostic tool in cases of prediabetes and diabetes in the country, as well as a good predictor of lipid profile [23][24][25] . A positive association of HbA1c has been reported with macro and microvascular complications of diabetes mellitus type 2 26 .…”
Section: Discussionmentioning
confidence: 99%